A Design of Intervention for the Communication and Assistance Improvement in a Dental Public Cabinet - Rodriguez-Priego, Maria Esther; Perez-Ortiz, Dario; Rodriguez-Priego, Nuria (Richtmann Publishing, 2012)
In public dental cabinets patients often miss their appointments which may cause dead time, resulting in material andpersonnel costs. The time lost estimated in a dental clinic from the Andalusian health service in Spain has an average of 27 minutes aday. This time is often employed in the treatment of patients who attend without an appointment, categorized as an ‘emergency’ (70patients per month in 2011, quoted time spent 38 minutes a day). 67% of these were patients who had not attended to their previousappointments. We analyzed surveys concerning patients´ satisfaction and complaints carried out in public health centers, the reasonswhy patients were attending without an appointment or for ‘emergencies’, as well as the communication channels between patient vs.dental care professional, and patient vs. appointment administration personnel. As a result, the process designed involves all theprofessionals, beginning at reception where patients will be reported concerning the way to cancel or postpone an appointment. Theincrease of the consultation time scheduled, will achieve an acceptable waiting time less than a week. Posters designed give detailedinformation with reference to office hours, how to cancel appointments, the ‘criteria’ and specific schedule for attending without anappointment. Specific schedule to attend emergencies, will take advantage to educate patients on schedule adherence, providing themwith another appointment in the shortest time possible. A design for the implementation of the communication between patients andprofessionals will improve the daily dynamics of the dental office.